Jaskra u chorego z guzem przysadki – opis przypadku - Lesiewska-Junk, Hanna; Malukiewicz, Grażyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Ocular hypertension and visual field loss would usually be thought sufficient to suspect glaucoma. A case is presented which illustrates the continuing need for vigilance in circumstance of an apparently straightforward diagnosis has been made.